Differential effects of the Affordable Care Act on the stage at presentation and receipt of treatment for pancreatic adenocarcinoma. Issue 4 (14th June 2022) - Hao, Scarlett; Mitsakos, Anastasios; Popowicz, Patrycja; Irish, William; Snyder, Rebecca A.; Parikh, Alexander A.
Abstract: Background and Objectives: For pancreatic ductal adenocarcinoma (PDAC) which lacks a recommended screening modality, the benefit of the Affordable Care Act (ACA) may not be an earlier diagnosis, but rather improved rates of treatment. The objective of this study was to examine change in the stage of PDAC presentation and treatment disparities following the ACA. Methods: A retrospective cohort study of patients with primary PDAC identified in the 2004–2017 National Cancer Database was divided into pre‐ and post‐ACA, for which the primary outcomes of a stage of presentation, receipt of surgical resection, and systemic therapy (termed multimodality) (Stage I–II), and receipt of systemic therapy (Stage III–IV) were compared by multivariable analysis. Results: 228, 015 patients were included. Odds of presenting with Stage I–II PDAC were significantly higher in 2011–2017 versus 2004–2010 (odds ratio 1.44, 95% confidence interval 1.40–1.47). Black patients with early‐stage disease had a lower likelihood of multimodality therapy and those with advanced disease were less likely to receive systemic therapy, before and after the ACA. Uninsured patients were less likely to receive any therapy compared with insured patients; this disparity increased in the post‐ACA period. Conclusions: An earlier presentation of PDAC increased following the ACA. However, racial, insurance, and socioeconomic treatment disparities persist.